The role of histamine in neurogenic inflammation. (15th August 2013) - Rosa, A C; Fantozzi, R
<x xml:space="preserve">Abstract</x> The term 'neurogenic inflammation' has been adopted to describe the local release of inflammatory mediators, such as substance P and calcitonin gene‐related peptide, from neurons. Once released, these neuropeptides induce the release of histamine from adjacent mast cells. In turn, histamine evokes the release of substance P and calcitonin gene‐related peptide; thus, a bidirectional link between histamine and neuropeptides in neurogenic inflammation is established. The aim of this review is to summarize the most recent findings on the role of histamine in neurogenic inflammation, with particular regard to nociceptive pain, as well as neurogenic inflammation in the skin, airways and bladder. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1